HIERARCHY AND HETERARCHY IN BRAZIL'S URBAN NETWORK (Brazilian Geographical Journal, 2014)
The ideas of urban hierarchy and heterarchy are discussed in this paper so as to further analyze what composes the present-day Brazilian urban network. Brazil is a vast country, whose land occupation is still in process, and its urban network quick and constant, to say the least. The increase in possibilities of spatial interaction by means of new data and communication technologies in turn make these dynamics ever so intense, thus amplifying the possibilities of multi-scale articulations not only vertically in cities of of different sizes and importance, but also horizontally and cross-sectionwise. The Brazilian urban network, due to its capital actions which promote processes under which territories are produced unequally, has been structured in a most intense manner. Different roles are attributed to cities in the urban network according to their spatial and economic concentrations in each one of those cities, therefore composing a city network which is diverse and uneven, in which spatial hierarchy continues to grow. The reproduction of capital does in fact promote this sort of structure, at the same time as the complexity of spatial and inter-scale interactions expand, thus generating complex articulations which lead us to adopt an idea of complementation of urban hierarchy; the very same methodological purpose of urban hierarchy.